From Le sacre to Les noces: Primitivism and the Changing Face of Modernity - Berman, Nancy (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
The function of the primitivist aesthetic in modern French culture shifted dramatically from the pre- to the post-war period. Whereas the primitivism of the Ballets russes's Le sacre du printemps was understood by its contemporaries to be radical, excessive, even prophetic and apocalyptic, the primitivism of Les noces was perceived to some extent as a manifestation of both the classicist "call to order" and the mechanistic aesthetic of the post-war period. Indeed, Les noces was one of many cultural products by means of which post-war modernists extolled the virtues of the machine age.